INtravenous Contrast computed tomography versus native computed tomography in patients with acute Abdomen and impaired Renal functiOn (INCARO): a multicentre, open-label, randomised controlled trial - study protocol. Issue 10 (6th October 2020) - Räty, Panu; Mentula, Panu; Lampela, Hanna; Nykänen, Taina; Helanterä, Ilkka; Haapio, Mikko; Lehtimäki, Tiina; Skrifvars, Markus B; Vaara, Suvi T; Leppäniemi, Ari; Sallinen, Ville
Abstract : Introduction: CT is the primary imaging option for acute abdominal pain in adults. Intravenous (IV) contrast media use improves CT quality but may cause post-contrast acute kidney injury (PC-AKI). Retrospective studies show no association between reduced baseline renal function and IV contrast CT, but, to our knowledge, no data from randomised controlled trials exist. Methods and analysis: The INCARO (INtravenous Contrast computed tomography versus native computed tomography in patients with acute Abdomen and impaired Renal functiOn) trial is a multicentre, open-label, parallel group, superiority, individually randomised controlled trial comparing IV contrast-enhanced CT to native CT in patients requiring emergency abdominal or body CT with impaired renal function defined as an estimated glomerular filtration rate (eGFR) of 15 to 45 mL/min/1.73 m 2 . The primary outcome is a composite of all-cause mortality or renal replacement therapy (RRT) within 90 days from CT. Secondary outcomes are AKI measured by KDIGO (The Kidney Disease: Improving Global Outcomes) criteria within 72 hours from CT, organ dysfunction defined by mSOFA (modified Sequential Organ Failure Assessment) criteria after 48 hours from CT, alive and hospital-free days within 90 days after CT, and time from imaging to definitive treatment. All-cause mortality, need for RRT and renal transplant in long-term follow-up are also measured. The calculated sample size is 994 patients. Patient recruitment is estimated to take 3 years. Ethics and dissemination: The Ethics Committee of Helsinki University Hospital approved the study. The findings will be disseminated in peer-reviewed academic journals. Trial registration number: NCT04196244